First To File Principle in Goto Brand Dispute Settlement (Case Study: PT. Terbit Financial Against Gojek and Tokopedia) - Achmad Maulana M; Dwi Desi Yayi Tarina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research with the title First To File principle in the resolution of GOTO brand disputes aims to find out how the dispute resolution against trademarks should use the First To File principle. This article uses normative legal research with a legal and conceptual approach. Trademark registration in Indonesia adheres to a constitutive system, as stated in Article 13 of Law Number 20 of 2016 concerning Marks and Geographical Indications where the applicant whose application is submitted first and registered first, then that party is entitled to the protection of the mark. However, in practice there are not a few disputes that arise due to the similarity of naming the brand. However, in practice, there are many disputes that arise due to similarities in naming brands or similarities in essence. Therefore, it is necessary to have legal certainty for rights holders who have registered their trademarks first.